An efficient method for density measurement for high-tightness woven fabrics. Issue 3 (February 2017) - Zhang, Jie; Pan, Ruru; Wang, Jingan; Gao, Weidong; Han, Yaobin
To measure the warp and weft densities of high-tightness fabrics, an efficient inspection method utilizing a novel density–texture formulation is developed. The density–texture relationship of twill and satin weaves is analyzed, and a formulation based on the weft and wale densities is developed and applied to calculate the warp density. In the experiment, the weft and wale densities are detected using a projection method on separately acquired transmittance images, and the warp density is calculated using the density–texture formulation. Experimental results proved that the proposed method is effective for measuring yarn densities of high-tightness fabrics with twill and satin weaves under realistic production conditions and can satisfy the requirement for production practice.